Impact of High Thermal Setting and Fluid Activities on Sandstone Compaction: A Case Study of the Baiyun Sag in the Pearl River Mouth Basin (Northern South China Sea) - Chi Li; Jinglan Luo; Caiwei Fan; Shanshan Li; Shijiu Wu; Chuan Lei; Kunpeng Song (Geofluids)
Compaction is regarded as central to the reduction of reservoir physical properties. The thermal compaction process controlled by a basin’s heat flow and the static compaction caused by overload on rocks are both important factors controlling the compaction strength. However, porosity loss resulting from thermal and static compaction has not been distinguished. The Baiyun Sag in the Pearl River Mouth Basin in the northern part of the South China Sea with high heat flows and a variable geothermal gradient is an ideal setting for studying the characteristics and mechanisms of the thermal compaction process. The characteristics of compaction and the effect of thermal fluid activities on reservoir physical properties are carried out, based on the observation and identification of sandstone thin sections under a microscope, the measurement and simulation of the temperatures and trapping pressures of fluid inclusions, and the calculation of the compaction porosity loss as well. The result shows that the compaction mode of sandstone reservoirs in the Zhuhai Formation is dominated by static compaction in the LGR (the low geothermal gradient region), whereas the diagenetic process of the Zhuhai Formation in the MGR (the moderate geothermal gradient region) and HGR (the high geothermal gradient region) is affected not only by the static compaction effect but also by the thermal compaction effect caused by abnormal formation temperature and pressure conditions. The porosity loss caused by the thermal compaction ranges from 5.5% to 11.2% with an average of 7.9% and from 4.6% to 16.6% with an average of 10.2% in the MGR and HGR, respectively. The porosity loss caused by the static compaction ranges from 15.9% to 20.8% with an average of 19.4% and from 8.4% to 15.8% with an average of 12.8% in the MGR and HGR, respectively.